UJI PEMBERIAN KOMPOS TANDAN KOSONG SAWIT DAN NPK 16:16:16 PADA PEMBIBITAN KELAPA SAWIT(Elaeis guineensis Jacq.) MAIN NURSERY DENGAN MEDIA SUB SOIL ULTISOL - Aminullah Aminullah; T. Rosmawati; Sulhaswardi Sulhaswardi (UIR Press, 2017)
The purpose of this research is to know the influence of compost TKKS and NPK 16:16:16 on the breeding of oil palm (Elaeis guineensis Jacq.) in Main Breeding with Sub Soil Ultisol Media. This research has been conducted in the field of Agriculture Faculty of the Islamic University of Riau. for 4 months, starting from April to August 2017. The design used in this research is Factorial Random Design (RAL) consisting of two factors, the first factor is Giving of empty palm fruit bunch compost (Factor K) consisting of 4 levels ie not giving empty bunches of palm oil (K0), giving compost of oil palm empty bunch 90 gr/plant (K1), 180 gr/plant (K2) and 270 gr/plant (K3), and NPK 16:16:16 Fertilizer (Factor P) consisting of 4 levels ie not giving fertilizer (P0), NPK 16:16:16 15 g/plant (P1), 30 gr/plant (P2), 45 gr/plant (P3) and 60 gr/plant (P4). The parameters observed in this study were the increase of plant height (cm), the increase of the number of stem (strands), the length of the longest stem length (cm), the increase of girth (cm), the number of root root (root) and root length (cm). The result of the research showed that the interaction of TKKS compost and NPK 16:16:16 fertilizer gave a significant effect on the plant height increase, the increase of midrib, the length of the longest bark and the increase of girth. Combination of best treatment on compost TKKS 270 g/plant and NPK 16:16:16 60 g/plant (K3P4) fertilizer. The main effect of TKKS compost and NPK 16:16:16 fertilizer gave a significant effect on all parameters in the range of plant height, the increase of midrib, the length of the longest stem, the increase of girth, the number of root roots and the longest root length. With the best treatment is the compost TKKS 270 g/plant (P3) and fertilizer NPK 16:16:16 60 g/plant (P4).